2016
DOI: 10.1039/c6fo01067a
|View full text |Cite
|
Sign up to set email alerts
|

Vascular- and hepato-protective effects of passion fruit seed extract containing piceatannol in chronic high-fat diet-fed rats

Abstract: The effects of chronic administration of piceatannol-enriched (9.5% w/w) passion fruit seed extract (PFSE) on the cardiovascular damage induced in a high-fat (HF) diet-fed model of Fischer 344 rats were evaluated. Rats were fed the control, HF, or HF diets containing PFSE (0.5% w/w) for 16 weeks, and the effects of the various diets on the tissue weight, serum lipid profile, hepatic fibrosis, hepatic ductular reaction, cardiac function and aortic ring reactivity were examined. HF diet-fed rats developed signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In ethanol-induced liver injury, treated daily with fruit juices to mice for 15 days could protect ethanol-induced liver injury by decreasing AST and ALT in liver, and alleviating the inflammation, oxidative stress (Zhang et al, 2016). In addition, the passion fruit seed extract prevented non-alcoholic fatty liver disease by improving the liver hypertrophy and hepatic histology of the high-fat diet-fed rats (Ishihata et al, 2016). In a pulmonary fibrosis of C57BL/6J mice model induced by bleomycin, administration of passion fruit peel extract significantly reduced loss of body weight and mortality rate, decreased the count of inflammatory cells, macrophages, lymphocytes, and neutrophils, reduced MPO activity and restored bleomycin induced depletion of SOD activity.…”
Section: Hepatoprotective and Lung-protective Activitiesmentioning
confidence: 99%
“…In ethanol-induced liver injury, treated daily with fruit juices to mice for 15 days could protect ethanol-induced liver injury by decreasing AST and ALT in liver, and alleviating the inflammation, oxidative stress (Zhang et al, 2016). In addition, the passion fruit seed extract prevented non-alcoholic fatty liver disease by improving the liver hypertrophy and hepatic histology of the high-fat diet-fed rats (Ishihata et al, 2016). In a pulmonary fibrosis of C57BL/6J mice model induced by bleomycin, administration of passion fruit peel extract significantly reduced loss of body weight and mortality rate, decreased the count of inflammatory cells, macrophages, lymphocytes, and neutrophils, reduced MPO activity and restored bleomycin induced depletion of SOD activity.…”
Section: Hepatoprotective and Lung-protective Activitiesmentioning
confidence: 99%
“…Piceatannol, a stilbene abundantly found in passion fruit seeds, reportedly exhibits a variety of biological activities [23]. Recently, we reported that the piceatannol in PFSE prevents high fat diet–induced cardiovascular disease and promotes neural stem cell differentiation to astrocytes [45,46]. In addition, the antiproliferative effects of piceatannol against some cancer cells have been well studied, and several pathways leading to piceatannol-induced apoptosis have been elucidated [21].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that piceatannol can also limit fat deposition in Caenorhabditis elegans [ 30 ] and in mice fed a high-fat diet [ 31 ]. Additional reports have also been published on piceatannol’s ability to lower circulating lipids in the spontaneously obese Zucker rats [ 11 ] and in high-fat diet fed Fisher rats [ 32 ], although without reducing their body weight gain. Thus, piceatannol, structurally similar to resveratrol but less studied for its anti-obesity actions, exhibits potential interest to limit the development of fat stores in vivo.…”
Section: Discussionmentioning
confidence: 99%